12x-2x+60=12x+40

Simple and best practice solution for 12x-2x+60=12x+40 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x-2x+60=12x+40 equation:


Simplifying
12x + -2x + 60 = 12x + 40

Reorder the terms:
60 + 12x + -2x = 12x + 40

Combine like terms: 12x + -2x = 10x
60 + 10x = 12x + 40

Reorder the terms:
60 + 10x = 40 + 12x

Solving
60 + 10x = 40 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
60 + 10x + -12x = 40 + 12x + -12x

Combine like terms: 10x + -12x = -2x
60 + -2x = 40 + 12x + -12x

Combine like terms: 12x + -12x = 0
60 + -2x = 40 + 0
60 + -2x = 40

Add '-60' to each side of the equation.
60 + -60 + -2x = 40 + -60

Combine like terms: 60 + -60 = 0
0 + -2x = 40 + -60
-2x = 40 + -60

Combine like terms: 40 + -60 = -20
-2x = -20

Divide each side by '-2'.
x = 10

Simplifying
x = 10

See similar equations:

| (3x-1)(5x+4)-15x*15x=17 | | 5x-10+60=180 | | 6y-2x+5=0 | | 4x-2(x-2)=-6+4x+2 | | 10h+25=90 | | 3/4n+7=10 | | -ab-3a^2b^2= | | 67654+98786= | | 187.92=6(007m+20.70+0.3(20.70)) | | 10x=56000-5000 | | 2x-40x=200 | | e^2x+1=10e^5x | | (X-2-5i)(x-2+5i)= | | 200.25=(x+7.90+4.90)15 | | -4x+2(x-3)=7x-12 | | U-7.1=6.11 | | 30+y=2y+15 | | X^2-98x+2392=0 | | 3(y+1)+2y=5(y-1+5) | | 0.3x=x-7 | | 6(6x-5)=22 | | 4xy=24 | | 13x-13=155+x | | -18-x=42+3x | | 5=13h | | Y=5.00+.40x | | 3(3x+6)=9x+18 | | 3x=20.5 | | -8x+x=27 | | -8.8(x-2.75)=17.6 | | -12x-8=21-11x | | (x/9)=-7x+8x-100-36 |

Equations solver categories